Caribbean transnational family - Wiltshire, Rosina (WAND, 2011)
Argues that migration as a major factor of Caribbean life and survival does not lead to the break up of the Caribbean family, but to the creation of a Caribbean transnational family.
Keywords: FAMILY; MIGRATION; HOUSEHOLD; SAINT VINCENT AND THE GRENADINES; GRENADA; TRINIDAD AND TOBAGO; CARIBBEAN